Physiological profiles associated with ceasing growth of unfertilized eggs produced by unmated queens in the subterranean termite Reticulitermes chinensis - Li, Ganghua (Biol Open, 2016)
In Reticulitermes chinensis, a close relative of R. speratus with asexual queen succession, unfertilized eggs can be produced but do not hatch as larvae. To explain this phenomenon, we analyzed the physiological differences between unfertilized eggs/unmated queens and fertilized eggs/mated queens. Fertilized eggs had significantly lower quantities of five amino acids (Cys, Met, Ile, Leu and Tyr), Ca, protein and cholesterol during development. The higher levels of four trace elements (Na, K, Zn and Fe) in fertilized eggs and their lower levels in mated queens indicated that mated queens might transfer these trace elements to fertilized eggs to aid development. The higher levels of Mn, triglycerides and serotonin in mated queens and higher levels of Mn and glucose in fertilized eggs suggested that these substances are very important for normal ovarian and embryonic growth. The different expression of three reproductive genes (vtg 1, rab 11 and JHE 1) suggested that they might be involved in the regulation of ovarian and embryonic growth. Overall, changes in these physiological indices may substantially affect ovarian and embryonic growth and inhibit development of unfertilized eggs in R. chinensis.